Fatou and Julia like sets - Charak, K. S.; Singh, A.; Kumar, M. (Ukrains’kyi Matematychnyi Zhurnal, 2026)
UDC 517.5For a familiy of holomorphic functions on an arbitrary domain, we introduce Fatou and Julia like sets, and establish some of their interesting properties.